Knowledge and attitudes of final year nursing students of National School of Nursing, Sri Jayewardenepura and School of Nursing, Colombo on infusion phlebitis - Harshani, R.A.T.; Perera, P.P.R. (Proceedings of the Scientific Sessions 2016, FMS, USJP in collaboration with SJGH, 2016)
Attached

Objectives: Knowledge on peripheral venous catheter related infection is important to help healthcare professionals to minimise the risk of infection. However nurses/students knowledge regarding this aspect has not been studied previously. Thus this study was carried out to evaluate the knowledge and attitudes of final year nursing students on infusion phlebitis. Methods: This descriptive cross sectional survey was carried out at National School of Nursing Sri Jayewardenepura and School of Nursing Colombo. A validated self-administrated questionnaire was applied. The questionnaire included 3 sections. Section “A” consisted of 3 questions about their educational background and gender. Section “B” consisted of 12 questions regarding knowledge on Phlebitis. Section “C” consisted of the attitudes scale regarding safe practice of cannulation which included 19 statements. Results: Final year students in both nurses training schools participated in the study and 216 questionnaires were collected. Most of the students were female (95.8%). Most of the students had fair knowledge (60.6%) and mean knowledge score was 48.8. They had favourable attitudes towards safe practice of cannulation except hand hygiene hnique (3.2%), type of gloves used during the procedure (3.7%), best place for documentation of cannulation - <j 8%) and selection of cannula (29.6%). Conclusions: The sample of student nurses’ knowledge to some areas on infusion phlebitis is inadequate. This could be a potential risk for patieint safety. Thus the subject should be more emphasized in training of student nurse